Crack Growth Analysis On Lattice Structure - Siti Shuhadah, Shamsul Anuar (Universiti Malaysia Sarawak (UNIMAS), 2020)
Lattice structure is a structure that consists multiple hollows shape that constructed by multiple same shape unit cell. Lattice structure become more prominent in industry as its advantages of lightweight, reduce cost and wastage, and have u~ique mechanical properties. Lattice structure can have many types of shape depending on the shape of unit cell. It can be gyroid, octet, full honeycomb, rectilinear and many more. Every material has its own limit before failure. As lattice structure become highly demand along with the move forward of additive manufacturing, the strength and its cracks need to be further analysed so that there is no excess load exerted on it. The tensile strength of the full honeycomb lattice structure is being made for infill density 0%- 100% for both normal dogbone shape and notched dogbone shape specimens. By analysing the strength of full honeycomb lattice structure, the relationship of the maximum tensile strength and its infill density is not proportional and fluctuating. 40% infill density have the highest maximum tensile strength and 20% infill density have the lowest maximum tensile strength. This study also focuses on the strength of the lattice structure that having a small crack. The strength of lattice structure is lower if there is any existing pre-crack A small crack can lead to fracture and failure. By observing under scanning electron microscope (SEM), pre-cracks also can make the lattice structure rupture severely.